(untitled) (Canadian Medical Education Journal, 2012)
Background: There is little published research about differences in doctor-patient communication of different specialties. Accordingly, we compared doctor-patient communication skills in two different specialties, general surgery (GS) and general practice (GP). Methods: Twenty residents training at the Bahrain Defence Force Hospital (10 men and 10 women; mean age 28 years; 10 GS and 10 GP) participated in 200 patient first visit consultations. The consultations were video-recorded and analysed by four trained observers using the MAAS Global scale. Results: 1) Internal consistency reliability of the MAAS Global (> 0.91) and Ep2 = 0.84 for raters was high, 2) GP residents spent more time (12 minutes) than GS residents (7 minutes), in the visits, 3) There were several differences on the MAAS Global items between GP and GS residents (GS > GP, p < 0.05 on history taking, diagnosis and medical aspects; GP > GS, p < 0.05 on information giving), and 4) The present participants performed well compared to normative samples as well as to criterion-referenced cut-off scores. The general level of communication skills in both specialties, however, was ‘unsatisfactory’ and ‘doubtful’, as it is for normative samples. Conclusion: Excellent doctor-patient communication is essential but does not appear to receive the amount of attention that it deserves in practice settings. There are some differences between specialties as well as unsatisfactory communication skills for both specialties, since residents from both programs spent less time than recommended on each consultation. Our findings emphasize the need to improve the communication skills of physicians in general and for surgeons in particular.